Systematic Literature Review: Pengaruh Kecerdasan Emosional terhadap Kinerja Karyawan - Aldri Frinaldi; Indah Permata Sari (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
Based on the research of previous researchers, the ratio of emotional intelligence has an effect on improving employee performance. The purpose of this literature study is to determine the relationship between emotional intelligence and employee performance. In this study, researchers will analyze various previous studies that have been conducted in this field. Search for articles using Google Scholar with keywords used in Emotional Intelligence on Employee Performance. The criteria for the articles used were published in the last 4 years, namely 2019-2022, the title and content are in accordance with the research objectives, the entire text and its relationship to employee performance and employee emotional intelligence. The result of the impact of emotional intelligence on employee performance is important in business operations and has an impact on the success of the entire organization. One's emotional intelligence has a significant influence on one's personal communication. Emotionally intelligent people are able to recognize emotions, manage emotions, motivate themselves, empathize, and socialize so they can communicate with others. Based on the results of this literature study, which is theoretically based on scientific evidence, it is very important to pay attention to the emotional intelligence of an employee because it plays a very important role in success.